2017
DOI: 10.11648/j.ijecs.20170201.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Communal Crises on Selected Crops Production Among Farmers in Langtang North Local Government Area of Plateau State, Nigeria

Abstract: Abstract:The study investigated the effects of communal crises on selected crops production among farmers in Langtang North local Government Area of Plateau State, Nigeria. Multi-stage sampling technique was adopted; four local government areas were selected in each of the local government selected, four villages affected by communal crises were selected purposively. In two of the villages selected, 24 respondents each (people affected by communal crises) were selected and 25 respondents each were also selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…With a regression coefficient for climate change p-value is 0.0001 which is below 0.05, communal clash has significant effect on respondent agricultural output in the study area this is in line with Ajayi et al (2020), who opined that communal clash had negative effect on yam production in Agatu Local Government Area of Benue State, Nigeria. This study is also in line with Kughur et. al (2017) who observed that conflicts have not only increased instability, but they have also shown a significant propensity to exacerbate the food crisis in Nigeria and other afflicted nations by causing farmers to lose their lives, animals, crops, and precious property.…”
Section: Discussion Of Findingssupporting
confidence: 93%
See 1 more Smart Citation
“…With a regression coefficient for climate change p-value is 0.0001 which is below 0.05, communal clash has significant effect on respondent agricultural output in the study area this is in line with Ajayi et al (2020), who opined that communal clash had negative effect on yam production in Agatu Local Government Area of Benue State, Nigeria. This study is also in line with Kughur et. al (2017) who observed that conflicts have not only increased instability, but they have also shown a significant propensity to exacerbate the food crisis in Nigeria and other afflicted nations by causing farmers to lose their lives, animals, crops, and precious property.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…Control of agricultural land and even pastoral resources is a key issue, and armed battles between factions have resulted in human deaths. (Kughur et. al 2017) Communal conflict must be linked to any sort of incompatibility, struggle, dispute, violence, or attacks that are fueled by communal attitudes or attachments in one way or another.…”
Section: Communal Conflictmentioning
confidence: 99%